Análise da associação entre desempenho socioambiental e disclosure socioambiental de empresas do setor elétrico brasileiro - Borges Junior, Pedro (2015)
The objective of this research is to analyze the association between the level of social-environmental disclosure and the social-environmental performance of firms of the Brazilian Power Supply industry, explained by the legitimacy theory. The methodology used was the content analysis of the social-environmental reports of Brazilian power supply industry firms. Also, ordinal logistic regression was used in order to analyze the probability of one company to be classified in higher levels of social-environmental disclosure how greater is the social-environmental performance, besides other economic variables We conclude that there is no evidence that the environmental performance exert influence on the likelihood of a company to be ranked higher or lower levels of disclosure. In this sense, there is evidence that the power companies analyzed have resorted to pragmatic and manipulative strategies legitimacy as defined by Suchman (1995) and Brinkerhoff (2005), since the level of environmental disclosure occurs regardless of the environmental performance of the company.